The Spark video collection : 2016. (O'Reilly Media, 2016)
"Subscribe to this ongoing compilation of Spark talks from leading developers and practitioners at Strata + Hadoop World conferences in 2016 (including San Jose, London, Beijing, New York, and Singapore). Receive an updated stream of talks covering the latest trends in Spark for real-time analytics and machine learning, as well as tips on how to deploy Spark in production. Topics range from Spark 2.0, anomaly detection with Spark, training deep networks in Spark, and tips for securing and scaling Spark in production. Subscribers will receive an updated group of the latest Spark talks after each Strata + Hadoop World conference in 2016."--Resource description page.